2014
DOI: 10.1161/circulationaha.113.004742
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Frequency Increase Rate Predicts Transition from Paroxysmal to Long-Term Persistent Atrial Fibrillation

Abstract: Background Little is known about the mechanisms underlying the transition from paroxysmal to persistent atrial fibrillation (AF). In an ovine model of long-standing persistent AF (LS-PAF) we tested the hypothesis that the rate of electrical and/or structural remodeling, assessed by dominant frequency (DF) changes, determines the time at which AF becomes persistent. Methods and Results Self-sustained AF was induced by atrial tachypacing. Seven sheep were sacrificed 11.5±2.3 days after the transition to persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
158
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(180 citation statements)
references
References 37 publications
13
158
1
8
Order By: Relevance
“…Our results are consistent with these experiments and further indicate that HL-1 cells maintained under spontaneously induced fibrillation present a reduction in I Na, I CaL , I to , and Cx43 ion channel gene expressions and an increase in I K1 gene expression, whereas nonfibrillating long-term HL-1 cell cultures did not present this gene expression remodeling, and, therefore, these changes can be attributed to fibrillationinduced remodeling and not culture time. This electrical remodeling is similar to what has been observed in the sheep atrial cardiomyocytes (20) and in patients with long-term AF (10). However, the analysis of other currents that may play an important role in AF remodeling (e.g., Cx40, Cx45, and I Kr ) did not show significant variations between early and late stages neither in the fibrillating group nor in the nonfibrillating group.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results are consistent with these experiments and further indicate that HL-1 cells maintained under spontaneously induced fibrillation present a reduction in I Na, I CaL , I to , and Cx43 ion channel gene expressions and an increase in I K1 gene expression, whereas nonfibrillating long-term HL-1 cell cultures did not present this gene expression remodeling, and, therefore, these changes can be attributed to fibrillationinduced remodeling and not culture time. This electrical remodeling is similar to what has been observed in the sheep atrial cardiomyocytes (20) and in patients with long-term AF (10). However, the analysis of other currents that may play an important role in AF remodeling (e.g., Cx40, Cx45, and I Kr ) did not show significant variations between early and late stages neither in the fibrillating group nor in the nonfibrillating group.…”
Section: Discussionsupporting
confidence: 87%
“…A critical obstacle for the elucidation of mechanisms responsible for chronic AF lies in the practical challenges associated with the development of experimental models that reproduce the electrophysiological characteristics of atrial remodeling. Animal models involve subjecting animals to weeks or months of sustained atrial arrhythmias, which implies significant economical, ethical, and time burdens (11,20). Other experimental models include in vitro cell cultures, which are typically obtained from neonatal rat hearts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a novel sheep model of long-term persistent AF, in which the tachypacing was stopped once AF was self-maintained [14], was used to indirectly corroborate the essential role of rotors in AF maintenance. This model reproduced the shortening in the dominant atrial cycle length (or an increase in the atrial dominant frequency) observed in persistent AF patients during the remodeling process [15]. Unfortunately, current mapping technology does not allow simultaneous evaluation of the global atrial activity and the tracking of each individual rotor which precludes the identification of the specific mechanisms responsible for AF maintenance.…”
Section: Experimental Models With Persistent Atrial Fibrillationmentioning
confidence: 89%
“…First, intensely remodeled and fibrotic atria are more difficult to ablate than normal atria. After an intense electrophysiological and structural remodeling during the transition from PAF to PsAF, 12 any region in the atrium is capable of maintaining PsAF. 13 Second, ablation approaches, even if often extensive, miss key regions that mechanistically maintain the fibrillatory activity.…”
Section: Article See P 530mentioning
confidence: 99%